2014
DOI: 10.1098/rsif.2013.0850
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive channels and bacterial cell wall integrity: does life end with a bang or a whimper?

Abstract: Mechanogated channels are fundamental components of bacterial cells that enable retention of physical integrity during extreme increases in cell turgor. Optical tweezers combined with microfluidics have been used to study the fate of individual Escherichia coli cells lacking such channels when subjected to a bursting stress caused by increased turgor. Fluorescence-activated cell sorting and electron microscopy complement these studies. These analyses show that lysis occurs with a high probability, but the prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 54 publications
3
37
1
2
Order By: Relevance
“…It is only recently that alternative types of death phenotypes have been observed. Similar to our findings, Reuter et al (25) observed there are various classes or phenotypes of cells after osmotic shock, with cells that lyse immediately and cells that slowly fade away. They draw similar conclusions that many of the cells have damaged cell walls, as opposed to being completely lysed, and are able to stay intact for several minutes after the shock before the cell wall loses integrity and fails.…”
Section: Discussionsupporting
confidence: 80%
“…It is only recently that alternative types of death phenotypes have been observed. Similar to our findings, Reuter et al (25) observed there are various classes or phenotypes of cells after osmotic shock, with cells that lyse immediately and cells that slowly fade away. They draw similar conclusions that many of the cells have damaged cell walls, as opposed to being completely lysed, and are able to stay intact for several minutes after the shock before the cell wall loses integrity and fails.…”
Section: Discussionsupporting
confidence: 80%
“…To restore the natural turgor, the MS channels open up and pump out the cytoplasmic osmolytes, including ionic entities. The gating process (opening and closing of the MS channels) and restoring of ΔΠ 0 happens in less than a millisecond (t * MS ) (10,11,22,23). Release of ions from cytoplasm to the external solution results in a conductance increase with respect to the analytefree solution, consistent with our results in SI Text, 3.…”
Section: Methodssupporting
confidence: 81%
“…These proteins, which in the case of E. coli, are majorly MscL and MscS channels, pump out different osmolytes (including ions, ATP, lactose, etc.) into the surrounding medium without any damage to the cell envelope and/or cell lysis (10,22,23). In contrast, on osmotic upshift, another group of osmoregulatory transporters is activated to restore the natural turgor pressure (e.g., by uptaking solutes from the surrounding) (12,21,24).…”
mentioning
confidence: 99%
“…MS channels recognize a wide range of mechanical stimuli, and play important role in many physiological functions including osmotic pressure, touch and pain sensation, hearing, blood pressure, cell volume regulation, proprioception and gravity sense (Martinac, 1993;Sackin, 1995;Sachs and Morris, 1998;Hamill and Martinac, 2001). Prokaryotic MS channels have been extensively studied in Escherichia coli which harbors several MS channels (Martinac et al, 1987;Berrier et al, 1989;Delcour et al, 1989;Booth et al, 2007;Edwards et al, 2012;Reuter et al, 2014). Mechanosensitive channels have been classified based on their ion conductance as mechanosensitive channels of large conductance (MscL), mechanosensitive channels of small conductance (MscS), mechanosensitive channels of mini conductance (MscM) and mechanosensitive channels of K + -selective (MscK) (Sukharev et al, 1994;Berrier et al, 1996).…”
Section: Introductionmentioning
confidence: 99%